Addressing Economic/Environmental Sustainability Trade‐offs in Procurement Episodes with Industrial Suppliers. Issue 5 (11th February 2020) - Saunders, Lance W.; Paul Brooks, J.; Merrick, Jason R. W.; Autry, Chad W.
Abstract : Literature supports that buyers can influence suppliers to adopt sustainable practices. Much of this literature, however, is descriptive and takes only the perspective of a buyer trying to diffuse sustainability into its supply base. Alternatively, this study augments the literature through the development of a prescriptive mathematical model that maximizes a supplier's expected revenue from making a bid to a large buyer, inclusive of a sustainability criterion. Specifically, the model uses decision theory to determine an optimal level of sustainability to integrate into a bid to balance economic vs. sustainable trade‐offs based on perceived buyer preference. To illustrate the model's utility, it is then applied to a rich scenario, using data from an industrial supplier bidding for a contract to distribute a fuel additive in Brazil by balancing the trade‐off between decreased carbon emissions and increased distribution cost. A sensitivity analysis is then performed to illustrate how different forms of the buyer's objective function would influence the propagation of sustainability into optimal supplier bids. The research thereby adds to our understanding of sustainable sourcing by prescriptively modeling both buyer and supplier perspectives, when analyzing how buyer preferences can drive supplier behavior.